2018
DOI: 10.1111/ijag.12554
|View full text |Cite
|
Sign up to set email alerts
|

Local ordering and interfacial structure between spinel crystal and aluminosilicate glasses from molecular dynamics simulations

Abstract: Molecular dynamics simulations were performed to investigate the interfaces of soda magnesia aluminosilicate glass and MgAl2O4 spinel crystals. The glass structures were first generated and characterized. It was found that the glass‐forming network consists of fourfold coordinated [SiO4] and [AlO4] tetrahedra connected through corner sharing with Na+ and Ca2+ acting as modifiers or charge compensators. The glass and crystal interfaces were then constructed on low energy spinel surfaces with special measures to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…As the crystal part is fixed in this study, the interface area consists of the terminated layer from crystal side and few angstroms of surface region within the glass region, which is generated and considered as glass bulk due to the periodic boundary condition. [27,28] As expected, the crystal surface terminations impact atomic reorganization in glass that comes directly in their contact. In Figure 5b, the two terminations of LS2(110) result in different z-density profiles for the two interface regions.…”
Section: Atomic Density Profiles Of Differently Terminated Ls2(001)/l...supporting
confidence: 60%
See 2 more Smart Citations
“…As the crystal part is fixed in this study, the interface area consists of the terminated layer from crystal side and few angstroms of surface region within the glass region, which is generated and considered as glass bulk due to the periodic boundary condition. [27,28] As expected, the crystal surface terminations impact atomic reorganization in glass that comes directly in their contact. In Figure 5b, the two terminations of LS2(110) result in different z-density profiles for the two interface regions.…”
Section: Atomic Density Profiles Of Differently Terminated Ls2(001)/l...supporting
confidence: 60%
“…[ 25 ] Rushton et al [ 26 ] showed distinct atomic density profiles of interfaces between sodium lithium borosilicate and different MgO/CaO crystal surfaces. Sun and Du [ 27 ] reported that in the MD simulated MgAl 2 O 4 /aluminoborosilicate glass [ 27 ] interface, a highly ordered [SiO 4 ] tetrahedron layer forms near Al‐terminated MgAl 2 O 4 crystal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rushton et al reported interfaces between sodium lithium borosilicate glasses and the MgO and CaO crystals and found that the borate and silicate polyhedral shows strong correlation on position and orientation . We have recently reported the interfacial behaviors between soda magnesia aluminosilicate glass and MgAl 2 O 4 spinel crystals and found that that aluminum ions changed from mainly fourfold coordination in the glass to five and sixfold coordination near the interface . This provides evidence of the influence of the crystal structure on that of the glass at the interface, which can be an initial stage of crystal growth.…”
Section: Introductionmentioning
confidence: 71%
“…Although the accessible time and length scales are limited, MD simulations have been successfully applied to investigate glass/ceramics interfaces and their composites. For example, Galiolini et al have devoted to understand adhesion between an oxide glass and Al 2 O 3 and Si 3 N 4 , Sun and Du have recently investigated an interlayer between an aluminosilicate glass and a MgAl 2 O 4 spinel crystal, and Lusvardi et al have tried to evaluate possibility of crystallization in some oxide glasses. Furthermore, fracture patterns in amorphous aluminum nano‐particles embedded soda‐lime silica glass have been investigated .…”
Section: Introductionmentioning
confidence: 99%